2022
DOI: 10.3390/ijms232113366
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Revealed Mitochondrial Dysfunction in Photoreceptor Cells under Hyperglycemia

Abstract: Diabetic retinopathy (DR) was identified as a leading cause of blindness and vision impairment in 2020. In addition to vasculopathy, DR has been found to involve retinal neurons, including amacrine cells and retinal ganglion cells. Despite possessing features that are susceptible to diabetic conditions, photoreceptor cells have received relatively little attention with respect to the development of DR. Until recently, studies have suggested that photoreceptors secret proinflammatory molecules and produce react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Defective mitochondrial biogenesis and changes in energy metabolic profile have been implicated in various cell types and tissues affected by type 2 diabetes ( Jheng et al, 2012 ; Forbes and Thorburn, 2018 ; Pinti et al, 2019 ). In addition, mitochondrial dysfunction has been observed in various retinal cells, including retinal endothelial cells, Müller cells, and photoreceptor cells under simulated hyperglycemia ( Trudeau et al, 2010 ; Tien et al, 2017 ; Lam et al, 2022 ). Recently, our lab has demonstrated a compromised mitochondrial biogenesis in the retina of db/db mice, in which functional and structural changes in the neuroretina were observed, compared to their non-diabetic heterozygous littermate ( Lam et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective mitochondrial biogenesis and changes in energy metabolic profile have been implicated in various cell types and tissues affected by type 2 diabetes ( Jheng et al, 2012 ; Forbes and Thorburn, 2018 ; Pinti et al, 2019 ). In addition, mitochondrial dysfunction has been observed in various retinal cells, including retinal endothelial cells, Müller cells, and photoreceptor cells under simulated hyperglycemia ( Trudeau et al, 2010 ; Tien et al, 2017 ; Lam et al, 2022 ). Recently, our lab has demonstrated a compromised mitochondrial biogenesis in the retina of db/db mice, in which functional and structural changes in the neuroretina were observed, compared to their non-diabetic heterozygous littermate ( Lam et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high metabolic activity and constant exposure to damaging light radiation may render the retina more vulnerable to oxidative stress under diabetic conditions. Therefore, there is growing interest in using antioxidants to treat DR. Our previous studies have demonstrated the involvement of mitochondrial dysfunction in DR using both in vitro and in vivo models ( Lam et al, 2022 , 2023 ). Similar findings have also been observed in other retinal cell types, such as retinal endothelial cells and Müller cells under simulated hyperglycemia ( Trudeau et al, 2010 ; Tien et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, KD has been proven to have a therapeutic effect on glucose levels after TBI (Ritter, Robertson et al 1996). Indeed, high-glucose levels have been associated with induction of mitochondrial dysfunction in cardiac models, retina, and neurons (Russell, Golovoy et al 2002;Dassanayaka, Readnower et al 2015;Fiorello, Treweeke et al 2020;Lam, Cheung et al 2022). Contrary to KD, in our experience, KE treatment alone does not change glucose levels to the same extent that KD does (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in proteomic research have made it possible to identify a set of proteins differentially posttranslationally modified in diseased retinas ( Garcia-Quintanilla et al, 2022 ; Lam et al, 2022 ; Lee et al, 2022 ; Nattinen et al, 2022 ; Smyczynska et al, 2022 ; Zhou H. et al, 2022 ). However, despite advancements in molecular knowledge regarding the retinal pathobiology of ocular diseases, the question of whether the differential expression of proteins associates with altered activity remains unaddressed.…”
Section: Posttranslational Modifications In the Retinamentioning
confidence: 99%